2014
DOI: 10.4103/2141-9248.129048
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and use of personal protective measures against mosquito borne diseases in a resettlement colony of Delhi

Abstract: Background:Mosquito borne diseases (MBDs) are major public health problem in India. State of Delhi is endemic for dengue and other MBDs. The increasing incidence of MBDs in Delhi in recent years warrants a pro-active approach for their prevention. Knowledge and use of personal protective measures (PPMs) presents an effective strategy for prevention and control of MBDs.Aim:The present study was conducted to assess the knowledge and use of PPMs against MBDs in an urban resettlement colony of Delhi.Subjects and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 5 publications
(11 reference statements)
7
46
0
Order By: Relevance
“…18 Anand T et al in his study conducted in a resettlement colony of central Delhi found that majority of the participants (68%) knew about the breeding site of anopheles and Dengue mosquito. 19 In comparison to above mentioned studies, the population of the present study had very poor awareness regarding breeding places of the mosquitoes. So this issue should be addressed immediately for better prevention of the diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Anand T et al in his study conducted in a resettlement colony of central Delhi found that majority of the participants (68%) knew about the breeding site of anopheles and Dengue mosquito. 19 In comparison to above mentioned studies, the population of the present study had very poor awareness regarding breeding places of the mosquitoes. So this issue should be addressed immediately for better prevention of the diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] A study done by Anand T et al in Delhi found that family and friends were most common source of information, and contrary to the findings of the present study. 19 Ghosh A et al in their study in Bankura town found that majority of the people (49.01%) had accumulated information regarding mosquito borne diseases from their daily observations on sick people. 20 This finding was contrary to most other studies and also the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were consistent with other studies in Delhi and Chennai. 8,10 As the vector of dengue bites during daytime it is essential to use these measures during the day time also. To conclude it can be stated that though many people are using PPMs, the preventive practices among the day biting mosquito is low which need to be corrected with proper health education.…”
Section: Resultsmentioning
confidence: 99%
“…6 These study findings were quite different from studies done in urban areas where a majority used liquid vapours and mats, for obvious reasons. 8,9 The PPMs were used mostly during night time. These findings were consistent with other studies in Delhi and Chennai.…”
Section: Resultsmentioning
confidence: 99%